The Impact of Monetary Connectivity: From Single Currency to Economic Growth - Widjanarko, Yeremia Nicolaus (Universitas Airlangga, 2024)
This research investigated the impact of the adoption of the Euro as a single currency in the European region (Eurozone) on transaction costs, consumption, investment, and economic growth. By combining monetary transmission theory, empirical data analysis, and case studies, this research revealed mechanisms that linked the single currency to increased economic activity and growth in the Eurozone. The results showed that the elimination of currency conversion costs, exchange rate uncertainties, and foreign currency risks had reduced transaction costs, encouraged cross-border trade, investment, and economic integration. The increase in transaction volume and value reflected an increase in household consumption, which in turn drove production, innovation, and further investment. The stability and confidence created by the European Central Bank and positive market expectations had contributed to sustained economic growth, as reflected in trend of the Eurozone’s gross domestic product (GDP). This research highlighted the transformative role of single currency system in promoting prosperity and economic stability across all member states. Keywords: Economic Growth, Euro, Eurozone, Monetary Connectivity, Monetary Transmission.